Effect of ArtinM on Human Blood Cells During Infection With Paracoccidioides brasiliensis - Ruas, Luciana P.; Genaro, Livia M.; Justo-Junior, Amauri S.; Coser, Lilian O.; de Castro, Lívia F.; Trabasso, Plinio; Mamoni, Ronei L.; Roque-Barreira, Maria-Cristina; Blotta, Maria-Heloisa S. L. (Frontiers in Microbiology, 2018)
Infections caused by fungi are prominent in our environment and can be potentially fatal. Paracoccidioidomycosis (PCM), caused by fungi of the Paracoccidioides genus, is the most frequent systemic mycosis in Brazil and the main cause of death among immunocompetent individuals. The antifungal therapy for PCM is usually effective but side effects and relapses are often reported. The latter could be avoided with alternative or complementary therapies aimed at boosting the immune response to combat this pathogen. Recent reports have pointed at the importance of an effective cellular immune response, with the participation of Th1 cells, in the resistance to and control of Paracoccidioides infection. The ArtinM lectin, extracted from jackfruit (Artocarpus heterophyllus) seeds, exhibits immunomodulatory activity against several intracellular pathogens, including P. brasiliensis, by promoting the development of a Th1 immune response. The aim of this work was to characterize the effect of ArtinM on peripheral blood cells of patients with PCM, and on those of control individuals infected with fungal yeasts cells in vitro. Our results demonstrate that ArtinM activates human neutrophils in vitro, leading to an increase in cytokine production and CD54 expression. ArtinM activated P. brasiliensis-infected neutrophils from both healthy individuals and patients with PCM. This activation was not dependent on the dectin-1 receptor, because pre-incubation with laminarin, a dectin-1 receptor blocker, did not reverse the activated state of the cells. ArtinM also stimulated human peripheral blood mononuclear cells to secrete proinflammatory Th1-related cytokines, which are protective against Paracoccidioides infection. These data support the immunostimulatory action of ArtinM, and encourage new studies using the lectin for the immunotherapy of paracoccidioidomycosis.